Intracerebral recording of readiness potential induced by a complex motor task - Rektor, I; Bares, M; Kanovský, P; Kukleta, M (Movement disorders, 2001)
While exploring 11 epileptic patients with intracerebral electrodes, we recorded readiness potential (RP) preceding a complex motor task. Multilead depth electrodes were positioned stereotactically into the cortex. In three patients, it was also possible to record RP from the putamen. The movement triggering the recording was the turning of a page in an architectural book. The movement was performed under two conditions: in the first condition, without looking at the pictures on the page (typical self-pacing); and in the second condition, following the inspection of the pictures. There were no significant differences in the appearance of RP under these two conditions, neither in duration nor in amplitude. That could be explained by the fact that "self-paced" does not mean "spontaneous," but covers the internal non-conscious program related to a given task. RP were present in the contralateral primary sensorimotor cortex and the bilateral supplementary motor area (SMA), and in the anterior caudal cingulate cortex. No difference between the cortical topography of RP preceding a simple motor task and the topography of RP occurring in connection with complex movement was observed.
Keywords: Epilepsy; implantované elektrody; epilepsie; Humans; motorické korové centrum; Dominance, Cerebral; mapování mozku; cingulární gyrus; Putamen; Female; Contingent Negative Variation; dospělí; lidé; putamen; mozková kůra; somatosenzorické korové centrum; Somatosensory Cortex; Cerebral Cortex; Brain Mapping; Adult; Electrodes, Implanted; dominance mozková; ženské pohlaví; Male; Motor Cortex; Psychomotor Performance; Gyrus Cinguli; mužské pohlaví; psychomotorický výkon; kontingentní negativní variace